Historic Preservation in Indiana : Essays from the Field - Clement, Kristen; Hiller, Nancy R. (Book collections on Project MUSE., 2013)
Since the second half of the twentieth century, historic preservation has been on the rise in American cities and towns, from urban renewal and gentrification projects to painstaking restoration of Victorian homes and architectural landmarks. In this book, the editor brings together individuals - with distinctive styles and perspectives - to talk about their passion for preservation. They consider the meaning of place and what motivates those who work to save and care for places; the role of place in the formation of identity; the roles of individuals and organizations in preserving homes, neighborhoods, and towns; and the spiritual as well as economic benefits of preservation. Richly illustrated, this is a book aimed at readers who care about preserving the past for future generations.